2016
DOI: 10.1016/j.jcms.2016.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Oral leukoplakia treatment with the carbon dioxide laser: A systematic review of the literature

Abstract: a b s t r a c tWe conducted a systematic review of the literature to evaluate treatment of oral leukoplakia with the carbon dioxide (CO 2 ) laser.A comprehensive search of studies published between 1981 and 2015 and listed in the PubMed (National Library of Medicine, NCBI) database yielded 378 articles which were screened in detail. Relevant studies were selected according to predetermined inclusion and exclusion criteria. A total of 33 articles met the final inclusion criteria and were analysed in detail in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 35 publications
(80 reference statements)
0
29
0
1
Order By: Relevance
“…1% to 40.7% and an MTR ranging from 0% to 15.4% when using a CO2 laser. 29 A retrospective study on 94 surgically excised lesions with cold knife performed by Holmstrup et al showed a recurrence rate of 13% and an MTR of 12% after a mean follow-up period of 7.5 years. 22 Surgical intervention with cold knife excision and/ or CO2 laser is usually reserved for nonhomogeneous OL, especially the erythroleukoplakic type; those associated with moderate to severe dysplasia; and the verrucous proliferative type.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1% to 40.7% and an MTR ranging from 0% to 15.4% when using a CO2 laser. 29 A retrospective study on 94 surgically excised lesions with cold knife performed by Holmstrup et al showed a recurrence rate of 13% and an MTR of 12% after a mean follow-up period of 7.5 years. 22 Surgical intervention with cold knife excision and/ or CO2 laser is usually reserved for nonhomogeneous OL, especially the erythroleukoplakic type; those associated with moderate to severe dysplasia; and the verrucous proliferative type.…”
Section: Introductionmentioning
confidence: 99%
“…The current surgical treatment modalities include cold knife excision, CO2/Nd:YAG/KTP lasers, or a combination of excision and laser treatment. 29 A recent systematic review of 33 studies by Mogedas-Vegara et al showed a recurrence rate of OL ranging from Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the field mapping during the phase of multiple biopsies sampling can be used in order to better define the histopathological features of the most severely affected PVL epithelial regions. 8,9 For this aiming, the punch biopsy of the oral cavity is a safe and useful technique that can be easily used by oral pathologist, with complications from surgery almost nonexistent and minor in degree. 10 Standardization of depth using the punch biopsy technique in OSCC is currently under investigation.…”
Section: Dear Editormentioning
confidence: 99%
“…Malign Potansiyel: Yapılan çalışmalarda, ağız mukozasında oluşan lökoplaki lezyonlarının malign transformasyon oranlarının %4.4-%17.5 arasında olduğu bulunmuştur [4,30]. Bu oranlar çok yüksek gibi görünmemekle birlikte, lökoplakili hastalarda kanser gelişme riski, diğer populasyondakilerden 50-100 kat daha fazladır [8,19].…”
Section: -Etiyolojisi Bilinmeyen Lezyonlar ''Idiopatik Lökoplakiler''unclassified